Temporary changes in STI & HIV testing & diagnoses across different phases of the COVID-19 pandemic, Chicago IL - Pyra, Maria; Schafer, Tommy; Rusie, Laura; Houlberg, Magda; Thompson, Hale M.; Hazra, Anu (Frontiers in Reproductive Health, 2023)
While the U.S. has seen a sustained rise in STI cases over the past decade, the impact of the COVID-19 on STIs and HIV is unclear. To examine the short- and medium-term impacts of COVID-19 and HIV and STI testing and diagnosis, we compared pre-pandemic trends to three periods of the pandemic: early pandemic, March-May 2020;, June 2020-May 2021; and late pandemic, June 2021-May 2022. We compared average number of monthly tests and diagnoses, overall and by gender, as well as the monthly change (slope) in testing and diagnoses. We find that after decreases in average monthly STI and HIV testing and diagnoses during the early and mid pandemic, cases were largely back to pre-pandemic levels by the late pandemic, with some variation by gender.